Hot carrier relaxation in GaN : LO phonon scattering and excitonic effects - O'Sullivan, E; Hess, S; Taylor, R; Cain, N; Roberts, V; Roberts, J; Ryan, J (1999)
Hot carrier relaxation has been studied in GaN using femtosecond time-resolved optical transmission and reflection. A non-thermal electron distribution with a pronounced "cut-off" at E-LO is observed for up to similar to 3 ps after photoexcitation. Monte Carlo simulations show that this behaviour is due to a remarkably strong electron-LO phonon interaction. Excitonic effects are also pronounced and strongly influence the dynamics. (C) 1999 Published by Elsevier Science B.V. All rights reserved.